2011
DOI: 10.1007/s10488-011-0364-x
|View full text |Cite
|
Sign up to set email alerts
|

Early Dropout from Psychotherapy for Depression with Group- and Network-model Therapists

Abstract: Administrative data were used to examine early dropout among 16,451 health plan members calling to request psychotherapy for depression. Compared to members referred to group-model therapists, those referred to network-model therapists were more likely to drop out before the initial visit (OR 2.33, 95% CI 2.17 – 2.50) but less likely to drop out after the first visit (OR 0.45, 95% CI 0.43 – 0.48). These differences were unaffected by adjustment for neighborhood income and educational attainment, antidepressant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…These data were collected for a larger study examining predictors of adherence to psychotherapy for depression (7). The study population included all members aged 13 and older requesting an initial psychotherapy visit for a chief complaint of depression between 1/1/2003 and 12/31/2008.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These data were collected for a larger study examining predictors of adherence to psychotherapy for depression (7). The study population included all members aged 13 and older requesting an initial psychotherapy visit for a chief complaint of depression between 1/1/2003 and 12/31/2008.…”
Section: Methodsmentioning
confidence: 99%
“…Among outpatients starting antidepressant treatment for depression, fewer than half continue medication through 12 weeks of acute-phase treatment (4–6). Among outpatients making an initial psychotherapy visit for depression, one third do not return for a second visit and fewer than half continue for four or more visits (7, 8). Increasing adherence to treatment is a central component of most successful depression care improvement programs (911).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Primary care providers in the United States are more than twice as likely to report problems with referral of patients with mental health problems to specialists than any other chronic condition [25]. Moreover, a large US study showed that only approximately 60% of patients referred by primary care doctors to mental health specialists actually followed through with the referral [26], and studies have shown that the mean number of appointments in those who do pursue a specialty mental health referral is two [27]. Thus, few patients who receive mental health care after primary care referral actually receive an adequate “dose” of mental health care.…”
Section: Gaps In Quality Of Mental Health Care In Primary Care Systemsmentioning
confidence: 99%
“…As few as 20% of patients started on antidepressant medications in “usual” primary care show substantial clinical improvement [34,35]. Many patients referred to psychotherapy receive an insufficient number of visits and/or ineffective forms of psychotherapy [27,36], so that treatment response for this type of treatment is also as low as 20% [34,36]. Finally, poor quality of medical care in patients with mental illness may explain a significant portion of their excess mortality [37].…”
Section: Gaps In Quality Of Mental Health Care In Primary Care Systemsmentioning
confidence: 99%